La domesticación del samurái : el individualismo honorífico y la construcción del Japón moderno - Ikegami, Eiko (Autores, textos y temas. Ciencias sociales, 2012)
This book demonstrates how Japan's so-called harmonious collective culture is paradoxically connected with a history of conflict. Ikegami contends that contemporary Japanese culture is based upon two remarkably complementary ingredients, honorable competition and honorable collaboration. The historical roots of this situation can be found in the process of state formation, along very different lines from that seen in Europe at around the same time. The solution that emerged out of the turbulent beginnings of the Tokugawa state was a transformation of the samurai into a hereditary class of vassal-bureaucrats, a solution that would have many unexpected ramifications for subsequent centuries.